Peningkatan Produktivitas Pembelajaran Bagi Kelompok Belajar Binaan Karang Taruna di Kota Surakarta - A Anditha Sari; Norma Puspitasari; Jahid Syaifullah (Universitas Mathla'ul Anwar Banten, 2018)
INCREASING LEARNING PRODUCTIVITY FOR STUDY GROUPS OF YOUTH ORGANIZATION IN SURAKARTA. The general conditions of non-formal education such as the current study group, the social activists of this society are certainly experiencing various obstacles, obstacles and problems as well as the ups and downs of its management, but they conclude that this social activity is seen as a challenge that must be addressed wisely so that they hope the existence of this learning group can continue to grow and develop in the future. This can be seen from many of his students in their respective areas who follow the learning group. Non-formal education groups targeted in the implementation of this PKM is the Study Group of “Rumah Anak Pintar” (RAP) in Kampung Sewu Village and Kratonan Learning Group. These two study groups are the guidance of the organization of youth. Identified partner issues are on education and socioeconomic fields. In the field of education, the ability of tutoring teacher is still limited to giving questions and corrections. There is no creative material such as storytelling and playing or the use of multimedia. The socio-economic problems are seen from the supporting infrastructure facilities in inadequate learning. This training activity is divided into two stages: (1) improvement of skills in learning (2) making multimedia-based teaching materials. The outcome of this activity is the making of multimedia-based teaching materials, skill enhancement in the delivery of story material and singing, as well as the provision of learning facilities.